A referenciação no sincretismo do YouTube: o caso dos vídeos que divulgam ciência - Zandonai, Marcos Filipe (Universidade do Vale do Rio dos Sinos, 2016)
In this thesis, I approach the phenomenon of referencing in scientific popularization videos of YouTube. I explode the nominations lexically expressed, collating them with the visual objects (graphic-digital designs and bodily movements) that compose the videos. I intent to understand the contribution of the nonverbal in the building of discourse objects, that is, to comprehend which are the functions undertaken by the visual elements in referencing. I define, thereby, two specific goals, namely: 1) to examine the cases of co-referentiality between lexicalized referential expressions and visual messages, verifying the semantic relations engineered by this union and 2) to investigate the verbal – nonverbal co-referentiality in what concerns its possible pragmatic effects, attained to the media community, which requires considering the referencing choices as being influenced by the situation of midiatization of science. The functioning of referencing is ascertained based on the classification of Cavalcante (2003) and others Text Linguistics authors that assume a constructivist and cognitive-discursive vision of textualization and referential phenomena (MONDADA, 2002; CAVALCANTE, 2011). The effects of anaphorization are seen based on studies the discourse of science midiatization (CHARAUDEAU, 2009; 2008), as this is the surrounding of language activity permeated by rituals and constraints that influence the enunciators of the videos in the lexical and semiotic choices and give clues on how they legitimate the meanings of science. The audiovisual text instances the coalescence of modalities of texts with semiotically distinct natures. For this reason, I consider it a syncretic text, which can be exploited according to the principles of semiotics Syncretic (BEIVIDAS, 2006; PIETROFORTE, 2008). I adopt the postulates of greimasian based Semiotics (GREIMAS and Courtes, 2013) in order to access the anaphoric chains, which are subsumed to meaning in a syncretic surface (with images as well as words), which requires a semiotically way of thinking (BARROS, 1990, 2001). I walk the nuances of nonverbal communication, using the analytical categories of Rector and Thirty (1985, 2005), that allow to characterize the bodily movements that also act on the referral of episodes, where the body of promoters (journalist and scientists) is used to create a kind of "drama", "theater" that aims to explain science. I choose to analyze videos of two YouTube channels (IbioMovies and Além da Bio), constituting the corpus with a video of each channel. The audiovisuals are mainly examined with respect to the body and theatrical movement. The video from Além da Bio, in particular, receives treatment with respect to the graphic-digital designs property. I undertake a qualitative analysis of these videos, which were selected due to the fact that they are nonverbal practices and to be diffusers of science content. I maintain that it is possible to check the points of co-referentiality between imagistic items on the one hand, and linguistic-verbal, the other, when references. I show semantic and cognitive factors linked to cohesion and consistency that make the "syncretic referencing" work, stressing the role that referring expressions meet ilocutionarily. I intent to advance in the understanding of gears and potentials of scientific communication in the "new media".
Keywords: Referenciação; Divulgação científica midiática; Semiótica; Comunicação não verbal; Referencing; Scientific popularization in the media; Semiotics; Nonverbal communication; ACCNPQ::Lingüística, Letras e Artes::Lingüística